THE EFFECT OF POST PARTUM EDUCATION ON PARENTING SELF-EFFICACY AND POST PARTUM BLUES IN PRIMIPARA MOTHERS POST SECTIO CAESAREA AT ESTOMIHI HOSPITAL, MEDAN C - Santi Widya Purba; Siti Maimunah; Gunarmi (Jurnal Penelitian, 2025)
Background: High parenting self-efficacy will reduce the risk of postpartum depression. The prevalence of depression 6 months postpartum overall is 4.0%, with a higher prevalence in urban areas (5.7%) than in rural areas (2.9%). Young mothers in urban and rural regions show different risk factors for postpartum depression. Meanwhile, mothers who have low parenting self-efficacy scores can increase the risk of postpartum depression, inability to care for babies, which will increase infant morbidity and mortality rates, marital conflict, lack of relaxing and enjoyable time with children, and experience great difficulties in carrying out baby care tasks. The purpose of this study is to determine the effect of postpartum education on parenting self-efficacy and postpartum blues in primiparous mothers after cesarean section. Method: This study is a Quasi-Experimental study with a pretest-posttest Non-equivalent control group design. The research method used is postpartum education with leaflets and lectures on parenting self-efficacy and postpartum blues. The study population is post-CS mothers at Estomihi Hospital, Medan. The sampling technique is purposive. The sample size is 38 respondents, consisting of 19 people in the experimental group and 19 people in the control group. Univariate and bivariate data analysis using the Wilcoxon test and ordinal regression test. Results: The statistical test results showed a decrease from the intercept-only model to the final model, namely 26.761 to 5.623, with a difference (Chi-square value) of 21.138, which means there is a real influence with the presence of independent variables. If seen from the significance value, there is a significant influence between postpartum education using leaflets on parenting self-efficacy and postpartum blues because the significance value obtained is 0.000 <0.05. Conclusion: There is a significant influence of postpartum education using leaflets on parenting self-efficacy and postpartum blues.